Extending Integration: Interventions Supporting Communication and Collaboration Between Patients with Neurological Diseases, Their Informal Caregivers and Healthcare Staff – a Scoping Review - Eskil Degsell; Lina Al-Adili; Petter Gustavsson; Mats Brommels; Petra Dannapfel (International Journal of Integrated Care)
Introduction: Addressing challenges due to demographic changes and the quest for improved value in healthcare requires an extended integrated approach to care that fosters collaboration between all stakeholders, especially within collaboration supporting cognitively impaired patients. The aim is to review existing studies on interventions to improve communication and collaboration between such patients, their caregivers and healthcare staff. Methods: Following PRISMA guidelines, we systematically searched electronic databases Medline (OVID), CINAHL (Ebsco), and Web of Science (Clarivate) for peer-reviewed literature [2010–2020] focusing on intervention studies. Papers were excluded if not assessing the impact of interventions or only presenting a study protocol. Results: Twelve studies explored diverse approaches to social support, all with the aim of improving communication and collaboration among stakeholders, and identified three intervention types: supporting empowerment, promoting collaborative disease management, and coping, and enhancing communication and relationships. Discussion: The interventions employed various approaches and assessed a range of outcomes, demonstrating the benefits of enhancing communication and collaboration among stakeholders. Yet only a few studies included the full triad of partners in care. Conclusion: There is still much to be done to achieve the extended integration of care services and support that will benefit from patient and caregiver involvement.